2015
DOI: 10.1016/j.chemosphere.2014.08.029
|View full text |Cite
|
Sign up to set email alerts
|

In vitro immune toxicity of polybrominated diphenyl ethers on murine peritoneal macrophages: Apoptosis and immune cell dysfunction

Abstract: h i g h l i g h t sPBDEs induced macrophage apoptosis. ROS levels were increased and GSH was depleted in PBDE-exposed macrophages. NAC could only partially attenuate the cytotoxicity of PBDEs. Both intrinsic and extrinsic apoptotic pathways were activated by PBDEs. Macrophage accessory cell function was inhibited by non-cytotoxic levels of PBDEs. a r t i c l e i n f o a b s t r a c tPolybrominated diphenyl ethers (PBDEs) are widely used as flame retardants and are often detected in the environment, wildlife, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 53 publications
(58 reference statements)
3
19
0
1
Order By: Relevance
“…The enhanced production of ROS can destroy the enzymatic activities that may be caused by decreased levels of glutathione (GSH) (Elumalai et al, 2007). This result is in agreement with previous studies (Livingstone et al, 1990;Stephensen et al, 2002;Lv et al, 2015). GR can catalyze GSSG to GSH to maintain the reduction potential (Gutteridge and .…”
Section: Possible Effective Mechanism Induced By Bde-47 Based On Glutsupporting
confidence: 90%
See 2 more Smart Citations
“…The enhanced production of ROS can destroy the enzymatic activities that may be caused by decreased levels of glutathione (GSH) (Elumalai et al, 2007). This result is in agreement with previous studies (Livingstone et al, 1990;Stephensen et al, 2002;Lv et al, 2015). GR can catalyze GSSG to GSH to maintain the reduction potential (Gutteridge and .…”
Section: Possible Effective Mechanism Induced By Bde-47 Based On Glutsupporting
confidence: 90%
“…One mechanism of injury involves ROS generation and reactions (He et al, 2008;Frouin et al, 2010;Yan et al, 2011). After exposure to PBDEs, the ROS contents were enhanced, and oxidative stress occurs (Livingstone, 1991;Stohs and Bagchi, 1995;Barata et al, 2005;Lv et al, 2015). The antioxidant defense system plays a critical role in protecting organisms from PBDEs-caused stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF- α can influence cell activity by activating caspase-8 and -10 [57]. Moreover, ROS activates caspase-3, -8, and -9, which are cysteine-dependent proteases that mediate cell death [58]. Caspase-9 directly influences caspase-3 activation, usually by interacting with caspase-8 [58].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the PBDEs are toxic to the liver activity (Zhou et al, 2002), thyroid and reproduction systems (Yu et al, 2015), nervous system (Costa et al, 2014) and immune system (Lv et al, 2015). Though some highly-toxic PBDEs have been banned in many countries, other PBDEs with relatively lower toxicity, such as BDE-209, are still largely produced and used in the world (Chen et al, 2012;Akortia et al, 2016).…”
Section: Introductionmentioning
confidence: 98%